Effects of Obesity on Bone Mass and Quality in Ovariectomized Female Zucker Rats - Rafaela G. Feresin; Sarah A. Johnson; Marcus L. Elam; Edward Jo; Bahram H. Arjmandi; Reza Hakkak (Journal of Obesity)
Obesity and osteoporosis are two chronic conditions that have been increasing in prevalence. Despite prior data supporting the positive relationship between body weight and bone mineral density (BMD), recent findings show excess body weight to be detrimental to bone mass, strength, and quality. To evaluate whether obesity would further exacerbate the effects of ovariectomy on bone, we examined the tibiae and fourth lumbar (L4) vertebrae from leptin receptor-deficient female (Leprfa/fa) Zucker rats and their heterozygous lean controls (Leprfa/+) that were either sham-operated or ovariectomized (Ovx). BMD of L4 vertebra was measured using dual-energy X-ray absorptiometry, and microcomputed tomography was used to assess the microstructural properties of the tibiae. Ovariectomy significantly (P<0.001) decreased the BMD of L4 vertebrae in lean and obese Zucker rats. Lower trabecular number and greater trabecular separation (P<0.001) were also observed in the tibiae of lean- and obese-Ovx rats when compared to sham rats. However, only the obese-Ovx rats had lower trabecular thickness (Tb.Th) (P<0.005) than the other groups. These findings demonstrated that ovarian hormone deficiency adversely affected bone mass and quality in lean and obese rats while obesity only affected Tb.Th in Ovx-female Zucker rats.